Electrode slurry and preparation method and application thereof
By adding graphite carbon balls with hollow structure as pore additives to the electrode slurry, a porous electrode with controllable porosity and compression elasticity is prepared, which solves the problems of complex preparation process and high cost in the prior art, and improves the stability and electrochemical performance of the electrode structure.
Patent Information
- Application Number
- CN202510219053.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to prepare porous electrodes with controllable porosity and compression elasticity, and the preparation process is complex, dangerous and costly, making it difficult to adapt to commercial applications.
A graphite carbon ball with hollow structure inside is added to the electrode slurry as the pore additive, and the electrode slurry is coated on the electrode current collector to prepare a porous electrode. By regulating the amount and characteristics of the pore additive, the pore size and mechanical characteristics of the electrode can be freely adjusted.
The porosity and compressible elasticity of the porous electrode are realized, the electrolyte wetting and ion transfer rate of the electrode are improved, and the structural stability of the electrode is enhanced. It is suitable for any silicon-based negative electrode or other positive and negative electrode materials with high stress.
Smart Images

Figure CN119890224A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of secondary batteries and relates to an electrode slurry and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have developed rapidly and are widely used. Currently, most commercial lithium-ion batteries use graphite as the negative electrode (372mAh / g) and lithium iron phosphate as the positive electrode (170mAh / g). Their energy density and power density are difficult to meet the development needs of the next generation of lithium-ion batteries. The silicon negative electrode has a capacity of up to 3579mAh / g, making it an ideal negative electrode for the next generation of lithium-ion batteries. However, the silicon negative electrode itself has a low electronic conductivity and a huge volume change during the charge and discharge process, resulting in poor stability of the electrode structure and rapid decay of the electrode's lithium storage capacity, which still needs further improvement.
[0003] At present, the method of introducing pores is usually used to promote the infiltration of lithium ions and stabilize the structure of the electrode. For example, the porous structure design is conducive to slowing down the volume expansion of the silicon-based negative electrode, enhancing the wettability of the electrolyte, and improving the lithium ion conductivity of the electrode. Among them, the typical porous silicon-carbon negative electrode uses porous carbon as a template, and silane is cracked by vapor deposition to generate silicon coated on the porous carbon surface. The porous silicon-carbon negative electrode prepared by this method has good structural stability, low electrode expansion rate, and good electrochemical performance.
[0004] However, the above preparation process cannot achieve precise control of the porosity and compressible elasticity of the porous electrode, and the preparation process is relatively dangerous and costly, which is not conducive to commercial application. Therefore, how to prepare a porous electrode with controllable porosity and compressive elasticity, and the preparation process is simple, safe, and low-cost, is an urgent problem to be solved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an electrode slurry and its preparation method and application. In the present invention, it is only necessary to add graphite carbon balls with a hollow structure inside as a pore additive during the preparation of the electrode slurry, and apply the electrode slurry on the electrode current collector to prepare a porous electrode. The preparation method is simple and can perfectly adapt to the current commercial electrode preparation process. In addition, since the size and mechanical properties of the pore additive are controllable, the size of the pores in the prepared porous electrode and the mechanical properties of the electrode can be freely regulated by using pore additives with different properties; at the same time, the porous electrode prepared by this slurry has the advantages of increasing the porosity of the electrode, improving the electrolyte wettability of the electrode and improving the ion transmission rate of the electrode, and the unique hollow carbon cage structure of the pore additive can also give the electrode good compressibility and resilience, so it can effectively buffer the volume strain of the electrode and enhance the structural stability of the electrode, and can be used for any silicon-based negative electrode or other positive and negative electrode materials with large stress.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an electrode slurry, the slurry comprising an active material, a conductive additive, a pore additive, a binder and a solvent;
[0008] The pore additive includes graphite carbon spheres, and the inside of the graphite carbon spheres has a hollow structure.
[0009] In the present invention, graphite carbon balls with a hollow structure inside are added to the electrode slurry as a pore additive. The hollow structure can improve the porosity of the electrode. The graphite carbon balls have good electrical conductivity, so the electronic conductivity of the electrode can be improved. At the same time, the unique hollow carbon cage structure of the pore additive can also give the electrode good compressibility and resilience, so it can effectively buffer the volume strain of the electrode and enhance the structural stability of the electrode. It can be used for any silicon-based negative electrode or other positive and negative electrode materials with large stress.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, based on the mass of the non-solvent part in the electrode slurry as 100wt%, the proportion of the pore additive in the non-solvent part of the electrode slurry is 0.1-2wt%, for example, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.3wt%, 1.5wt%, 1.8wt% or 2.0wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In the present invention, the porosity and compression elasticity of the electrode can be regulated by adjusting the amount of the pore additive added, thereby adjusting the electrical and mechanical properties of the porous electrode; by controlling the proportion of the pore additive in the non-solvent part of the electrode slurry within the range of 0.1 to 2 wt%, it is more conducive to improving the comprehensive performance of the porous electrode.
[0013] Preferably, the pore additive comprises heteroatom-doped graphitic carbon spheres.
[0014] Preferably, the heteroatom includes any one of a nitrogen atom, a boron atom, a sulfur atom, an oxygen atom or an aluminum atom, or a combination of at least two of them.
[0015] Preferably, the average particle size of the graphite carbon balls is 0.05 μm to 1 μm, for example, 0.05 μm, 0.07 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] Preferably, the wall thickness of the graphite carbon sphere is 5 to 20 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the pore size of the graphite carbon sphere is 0.05-1 μm, for example, 0.05 μm, 0.07 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, the mechanical properties and electrical properties of the electrode can be adjusted by regulating the average particle size, wall thickness and / or pore size of the graphite carbon balls. By controlling the average particle size of the graphite carbon balls within the range of 0.05 μm to 1 μm, the wall thickness within the range of 5 to 20 nm, and the pore size within the range of 0.05 μm to 1 μm, it is more conducive to making the electrode have better compressible elasticity, wettability to the electrolyte and conductivity.
[0019] In a second aspect, the present invention provides a method for preparing the electrode slurry as described in the first aspect, the preparation method comprising: uniformly mixing the pore additive, active material, conductive additive, binder and solvent to obtain the electrode slurry.
[0020] In the present invention, the electrode slurry with controllable mechanical and electrical properties can be obtained by simply mixing the pore additive, active material, conductive additive, binder and solvent. The preparation method is simple and suitable for commercial use.
[0021] Preferably, based on the mass of the non-solvent part in the electrode slurry as 100wt%, the proportion of the pore additive in the non-solvent part of the electrode slurry is 0.1-2wt%, for example, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.3wt%, 1.5wt%, 1.8wt% or 2.0wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the method for preparing the graphite carbon sphere comprises: introducing a carbon source into a quartz tube, depositing a graphitized carbon layer on a template by chemical vapor deposition to obtain a template / graphitized carbon layer composite, and then removing the template to obtain the graphite carbon sphere.
[0023] Preferably, the template comprises any one of silicon dioxide, magnesium oxide, zinc oxide, iron oxide or magnesium carbonate.
[0024] Preferably, the size of the template is 0.05-1 μm, for example, 0.05 μm, 0.07 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In the present invention, graphite carbon spheres with different pore diameters can be obtained by using templates of different sizes.
[0026] Preferably, the carbon source comprises a liquid carbon source or a gaseous carbon source.
[0027] Preferably, the liquid carbon source includes any one of acetonitrile, methanol or ethanol.
[0028] Preferably, the gaseous carbon source comprises methane or acetylene.
[0029] In the present invention, different heteroatoms can be doped by using different carbon sources, thereby achieving regulation of the conductivity of the electrode. The process is simple and easy to apply in practice.
[0030] Preferably, the heating rate of the chemical vapor deposition is 5 to 20°C / min, for example, 5°C / min, 7°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min, or 20°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the temperature of the chemical vapor deposition is ≥700°C, for example 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the chemical vapor deposition time is 20 to 180 min, for example 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, 140 min, 160 min or 180 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In the present invention, the wall thickness of the graphite carbon sphere can be adjusted by regulating the temperature and / or time of chemical vapor deposition, and can be selected according to needs in practical applications.
[0034] Preferably, the liquid carbon source is introduced into the quartz tube by an inert gas.
[0035] Preferably, the flow rate of the inert gas or the gaseous carbon source is 20 to 200 mL / min, for example 20 mL / min, 50 mL / min, 80 mL / min, 100 mL / min, 130 mL / min, 150 mL / min, 180 mL / min or 200 mL / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the inert gas or the gaseous carbon source is introduced before the heating begins, and the ventilation time is 10 to 20 minutes, for example, 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes or 20 minutes, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the method for removing the template comprises: etching the template in the template / graphitized carbon layer composite with a solvent to obtain the graphite carbon spheres.
[0038] Preferably, the solvent comprises sodium hydroxide solution.
[0039] Preferably, the concentration of the sodium hydroxide solution is 2.5-5 mol / L, for example, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L or 5.0 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In the present invention, sodium hydroxide solutions of different concentrations can be selected according to the mass proportion of the template in the template / graphitized carbon layer composite.
[0041] Preferably, the etching is performed under stirring.
[0042] Preferably, the etched product is washed with deionized water, filtered and dried.
[0043] Preferably, the preparation method comprises the following steps:
[0044] (1) Preparing graphite carbon spheres: placing a template in a quartz tube, introducing a carbon source into the quartz tube at a flow rate of 20 to 200 mL / min for 10 to 20 min, then heating the quartz tube to ≥700°C at a heating rate of 5 to 20°C / min, and depositing a graphitized carbon layer for 20 to 180 min to obtain a template / graphitized carbon layer composite, then preparing a 2.5 to 5 mol / L sodium hydroxide solution, placing the template / graphitized carbon layer composite in the sodium hydroxide solution, etching the template in the template / graphitized carbon layer composite, and then washing the product with deionized water, filtering and drying it in sequence to obtain the graphite carbon spheres;
[0045] (2) Preparing electrode slurry: The graphite carbon balls, active materials, conductive additives, binders and solvents described in step (1) are mixed evenly to obtain the electrode slurry.
[0046] In a third aspect, the present invention provides a porous electrode, comprising a current collector and a porous active material layer located on at least one side of the current collector, wherein the porous active material layer is obtained by coating the electrode slurry described in the first aspect or the electrode slurry prepared by the preparation method described in the second aspect onto at least one side of the current collector.
[0047] Preferably, the porous electrode comprises a porous negative electrode or a porous positive electrode.
[0048] The present invention does not limit the type of porous negative electrode or porous positive electrode. Exemplarily, the porous positive electrode includes any one of lithium iron phosphate positive electrode, lithium iron manganese phosphate positive electrode, lithium cobalt oxide positive electrode or ternary positive electrode, and the porous negative electrode includes any one of silicon-based negative electrode, carbon-based negative electrode, phosphorus-based negative electrode or tin-based negative electrode; the silicon-based negative electrode includes any one of micron silicon negative electrode, nano silicon negative electrode, silicon oxide negative electrode or silicon-carbon composite negative electrode, and the carbon-based negative electrode includes any one of graphite negative electrode or hard carbon negative electrode.
[0049] In a fourth aspect, the present invention further provides a method for preparing a porous electrode, the method comprising: coating the electrode slurry described in the first aspect or the electrode slurry prepared by the preparation method described in the second aspect onto at least one surface of the current collector.
[0050] In the present invention, a porous electrode with controllable porosity and compressible elasticity can be obtained by simply coating the conductive slurry onto a current collector. The preparation method is simple and suitable for commercial use.
[0051] In a fifth aspect, the present invention further provides a use of the porous electrode as described in the third aspect in a secondary battery.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The preparation method of the electrode slurry and the porous electrode provided by the present invention is simple. It only needs to add graphite carbon balls with a hollow structure inside as a pore additive during the preparation of the electrode slurry, and coat the electrode slurry on the electrode collector to prepare a porous electrode with controllable porosity and compressible elasticity, thereby improving the electrolyte wettability of the electrode and the ion transmission rate of the electrode, and can effectively buffer the volume strain of the electrode and enhance the structural stability of the electrode. It has a wide range of applications and can be used for any silicon-based negative electrode or other positive and negative electrode materials with large stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 It is a schematic diagram of the structure of the porous electrode in Application Example 1.
[0055] Figure 2 It is a schematic diagram of the preparation process of graphite carbon balls in Example 1.
[0056] Figure 1 In the figure: 1-active material; 2-conductive additive; 3-pore additive; 4-current collector. DETAILED DESCRIPTION
[0057] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0059] Example 1
[0060] This embodiment provides an electrode slurry, wherein the solid content of the slurry is 40wt%, the solvent is water, the non-solvent part is composed of 70wt% of silicon oxide powder, 14wt% of carbon black, 1wt% of graphite carbon balls and 15wt% of lithium polyacrylate solution (concentration is 6wt%), the pore diameter of the graphite carbon balls is 0.5μm, the wall thickness is 10nm, and the preparation method is as follows: Figure 2 As shown, a layer of graphitized carbon layer is first deposited on the template by chemical vapor deposition to obtain a template / graphitized carbon layer composite, and then the template in the template / graphitized carbon layer composite is etched under stirring conditions to obtain a graphite carbon sphere with a hollow structure inside. The specific process is as follows:
[0061] (1) Preparation of graphite carbon spheres: Weigh 5 g of silica powder with an average particle size of 0.5 μm and place it in a porcelain boat and spread it evenly. Place the porcelain boat on the furnace body of a tubular furnace and seal the quartz tube. Use argon gas to bring liquid acetonitrile carbon source into the quartz tube of the furnace body. The gas flow rate is 200 mL / min. Ventilate for 10 minutes to remove the air in the quartz tube. Raise the temperature of the furnace body to 900°C at a heating rate of 20°C / min and maintain at 900°C for 1 hour. Then wait for the furnace body to cool down to below 200°C, take out the porcelain boat, and repeatedly wash the reacted powder with 5 mol / L sodium hydroxide solution three times, then wash it once with deionized water, finally filter out the solid powder, and place the powder in a forced air drying oven to dry.
[0062] (2) Preparation of electrode slurry: Taking the mass of the non-solvent part in the electrode slurry as 100wt%, weigh 70wt% of silicon oxide powder (active material), 14wt% of carbon black (conductive additive), 1wt% of graphite carbon balls (pore additive) and 15wt% of lithium polyacrylate solution (concentration of 6wt%, binder) and place them in a bottle, add water (solvent) according to the mass proportion of the solvent in the slurry of 60wt%, stir evenly, and obtain electrode slurry.
[0063] Example 2
[0064] This embodiment provides an electrode slurry, the solid content of the slurry is 40wt%, the solvent is water, the non-solvent part is composed of 70wt% of silicon oxide powder, 14.9wt% of carbon black, 0.1wt% of graphite carbon balls and 15wt% of lithium polyacrylate solution (concentration is 6wt%), wherein the pore diameter of the graphite carbon balls is 50nm and the wall thickness is 5nm, and the preparation method is as follows:
[0065] (1) Preparation of graphite carbon spheres: Weigh 5 g of magnesium oxide powder with an average particle size of 50 nm and place it in a porcelain boat and spread it evenly. Place the porcelain boat on the furnace body of a tubular furnace and seal the quartz tube. Bring liquid methanol carbon source into the quartz tube of the furnace body with a gas flow rate of 200 mL / min. Ventilate for 10 minutes to remove the air in the quartz tube. Heat the furnace body to 700°C at a heating rate of 15°C / min and maintain it at 700°C for 20 minutes. Then wait for the furnace body to cool down to below 200°C, take out the porcelain boat, and repeatedly wash the reacted powder with 2.5 mol / L sodium hydroxide solution three times, then wash it once with deionized water. Finally, filter out the solid powder and place the powder in a forced air drying oven to dry.
[0066] (2) Preparation of electrode slurry: Taking the mass of the non-solvent part in the electrode slurry as 100wt%, weigh 70wt% of silicon oxide powder, 14.9wt% of carbon black, 0.1wt% of graphite carbon balls and 15wt% of lithium polyacrylate solution (concentration of 6wt%) and place them in a bottle, add water so that the mass proportion of the solvent in the slurry is 60wt%, to obtain electrode slurry.
[0067] Example 3
[0068] This embodiment provides an electrode slurry, the solid content of the slurry is 40wt%, the solvent is water, the non-solvent part is composed of 70wt% of silicon oxide powder, 13wt% of carbon black, 2wt% of graphite carbon balls and 15wt% of lithium polyacrylate solution (concentration is 6wt%), wherein the pore diameter of the graphite carbon balls is 1μm and the wall thickness is 20nm, and the preparation method is as follows:
[0069] (1) Preparation of graphite carbon spheres: Weigh 5 g of zinc oxide powder with an average particle size of 1 μm and place it in a porcelain boat and spread it evenly. Place the porcelain boat on the furnace body of a tubular furnace and seal a quartz tube. Pass gaseous methane as a carbon source into the quartz tube at a gas flow rate of 200 mL / min. Ventilate for 10 min to remove the air in the quartz tube. Raise the temperature of the furnace body to 1000°C at a heating rate of 20°C / min and maintain it at 1000°C for 3 h. Then wait for the furnace body to cool down to below 200°C, take out the porcelain boat, and wash the reacted powder repeatedly with 5 mol / L sodium hydroxide solution three times, then wash it once with deionized water, finally filter out the solid powder, and place the powder in a forced air drying oven to dry.
[0070] (2) Preparation of electrode slurry: Taking the mass of the non-solvent part in the electrode slurry as 100wt%, weigh 70wt% of silicon oxide powder, 13wt% of carbon black, 2wt% of pore additive and 15wt% of lithium polyacrylate solution (concentration of 6wt%) and place them in a bottle, add water according to the mass proportion of the solvent in the slurry being 60wt%, stir evenly, and obtain electrode slurry.
[0071] Example 4
[0072] The difference between this embodiment and embodiment 1 is that in this embodiment, the active material in the non-solvent part of the electrode slurry is silicon-carbon composite negative electrode powder, and in the preparation method, the silicon iodine powder in step (2) is replaced by silicon-carbon composite negative electrode powder.
[0073] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the non-solvent part of the electrode slurry is composed of 80wt% NCM811 powder, 9.5wt% carbon black, 0.5wt% graphite carbon balls and 10wt% polyvinylidene fluoride (concentration is 6wt%). In the preparation method, step (2) is: based on the mass of the non-solvent part in the electrode slurry as 100wt%, 80wt% NCM811 powder, 9.5wt% carbon black, 0.5wt% graphite carbon balls, and 10wt% polyvinylidene fluoride (concentration is 6wt%) are placed in a bottle, N-methylpyrrolidone (NMP) is added according to the mass proportion of the solvent in the slurry being 60wt%, and stirred evenly to obtain an electrode slurry.
[0076] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0077] Example 6
[0078] The difference between this embodiment and embodiment 1 is that in the non-solvent part of the electrode slurry, carbon black accounts for 14.95wt% and graphite carbon balls account for 0.05wt%. In the preparation method, 14.95wt% of carbon black and 0.05wt% of graphite carbon balls are added in step (2).
[0079] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0080] Example 7
[0081] The difference between this embodiment and embodiment 1 is that in the non-solvent part of the electrode slurry, carbon black accounts for 12wt% and graphite carbon balls account for 3wt%. In the preparation method, 12wt% of carbon black and 3wt% of graphite carbon balls are added in step (2).
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Example 8
[0084] The difference between this embodiment and embodiment 1 is that the pore size of the graphite carbon sphere is 5 μm, and the average particle size of the silicon dioxide powder in step (1) is 5 μm.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Example 9
[0087] The difference between this embodiment and embodiment 1 is that the wall thickness of the graphite carbon sphere is 2 nm, and the temperature is raised to 700° C. in step (1).
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 10
[0090] The difference between this embodiment and embodiment 1 is that the wall thickness of the graphite carbon sphere is 3 nm, and the temperature is maintained at 900° C. for 20 min in step (1).
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Embodiment 11
[0093] The difference between this embodiment and embodiment 1 is that the wall thickness of the graphite carbon sphere is 25 nm, and the temperature in step (1) is maintained at 900° C. for 5 h.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Comparative Example 1
[0096] The difference between this comparative example and Example 1 is that in the non-solvent part of the electrode slurry, the carbon black accounts for 15wt% and the graphite carbon balls account for 0wt%. In the preparation method, step (1) is not performed, and 15wt% of carbon black is added in step (2), but no graphite carbon balls are added.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 4 is that the carbon black accounts for 15wt% and the graphite carbon balls account for 0wt%. In the preparation method, step (1) is not performed, and 15wt% of carbon black is added in step (2), but no graphite carbon balls are added.
[0100] The rest of the preparation methods and parameters were the same as those in Example 4.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 5 is that the carbon black accounts for 10wt% and the graphite carbon balls account for 0wt%. In the preparation method, step (1) is not performed, and 10wt% of carbon black is added in step (2), but no graphite carbon balls are added.
[0103] The rest of the preparation methods and parameters were the same as those in Example 5.
[0104] Application Example 1
[0105] This application example provides a porous electrode and a lithium-ion battery containing the same, the structure of which is as follows: Figure 1 As shown, it includes a current collector 4 and a porous active material layer coated on one side of the current collector, the porous active material layer includes an active material 1, a pore additive 3 and a conductive additive 2, and the preparation method is as follows:
[0106] The electrode slurry prepared in Example 1 was coated on a copper foil using a 100 μm scraper. The copper foil was placed in a vacuum drying oven at 80° C. and dried for 5 h. After being taken out, it was pressed into small discs. The small discs were weighed and their mass was recorded. The small discs were placed in a glove box and button batteries were assembled.
[0107] Application examples 2-4, 6-11
[0108] The difference between Application Examples 2-4 and 6-11 and Application Example 1 is that the electrode slurry prepared in Examples 2-4 and 6-11 is coated on a copper foil.
[0109] The other preparation parameters were consistent with those in Application Example 1.
[0110] Application Example 5
[0111] The difference between this application example and application example 1 is that the electrode slurry prepared in example 5 is coated on aluminum foil.
[0112] The other preparation parameters were consistent with those in Application Example 1.
[0113] Comparative application example 1
[0114] The difference between Comparative Application Example 1 and Application Example 1 is that the electrode slurry prepared in Comparative Example 1 is coated on a copper foil.
[0115] The other preparation parameters were consistent with those in Application Example 1.
[0116] Comparative Application Example 2
[0117] The difference between Comparative Application Example 2 and Application Example 4 is that the electrode slurry prepared in Comparative Example 2 is coated on a copper foil.
[0118] The rest of the preparation parameters are consistent with those in Application Example 4.
[0119] Comparative Application Example 3
[0120] The difference between Comparative Application Example 3 and Application Example 5 is that the electrode slurry prepared in Comparative Example 3 is coated on aluminum foil.
[0121] The rest of the preparation parameters were consistent with those in Application Example 5.
[0122] Performance Testing
[0123] The long cycle performance of the battery was tested with a current density of 0.2C, and the cycle performance of the battery under high current was tested with a current density of 1C. The measured electrochemical properties of the battery are shown in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] From the data comparison between Application Examples 1-5 and Comparative Application Examples 1-3 in Table 1, it can be seen that after the electrode slurry provided in the present application is coated on the positive electrode or negative electrode current collector, the battery cycle performance is significantly improved compared to coating the electrode slurry without adding pore additives. This also shows that by using pore additives with different characteristics, the size of the pores in the prepared electrode and the mechanical properties of the electrode can be freely controlled, thereby effectively buffering the volume strain of the electrode, enhancing the structural stability of the electrode, and improving the battery cycle performance.
[0128] From the data comparison of Application Examples 6-7 with Application Example 1 in Table 1, it can be seen that when the proportion of the pore additive in the non-solvent part of the electrode slurry falls outside the range of 0.1-2wt%, the capacity retention rate of the battery after 200 cycles at 0.2C and 1C shows a downward trend. This is because the content of the pore additive in the electrode slurry will affect the porosity and compression elasticity of the electrode, and thus affect the electrical properties of the porous electrode.
[0129] From the data comparison between Application Examples 8-11 and Application Example 1 in Table 1, it can be seen that by adjusting the pore size and / or wall thickness of the graphite carbon balls, the mechanical properties and electrical properties of the electrode can also be adjusted; in the present invention, only the size of the template and the temperature and / or time of the chemical vapor deposition need to be changed to adjust the pore size or wall thickness of the pore additive, thereby adjusting the cycle performance of the battery. By controlling the pore size of the graphite carbon balls within the range of 0.05 μm to 1 μm and the wall thickness within the range of 5 to 20 nm, it is more conducive to making the electrode have better compressible elasticity, wettability to the electrolyte and conductivity.
[0130] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An electrode slurry, characterized in that: The slurry includes an active material, a conductive additive, a pore additive, a binder and a solvent; The pore additive includes graphite carbon spheres, and the inside of the graphite carbon spheres has a hollow structure.
2. The electrode slurry according to claim 1, characterized in that: Based on the mass of the non-solvent part in the electrode slurry being 100 wt %, the pore additive accounts for 0.1 to 2 wt % of the non-solvent part in the electrode slurry; Preferably, the pore additive comprises heteroatom-doped graphitic carbon spheres; Preferably, the heteroatom includes any one or a combination of at least two of a nitrogen atom, a boron atom, a sulfur atom, an oxygen atom or an aluminum atom; Preferably, the average particle size of the graphite carbon spheres is 0.05 to 1 μm; Preferably, the wall thickness of the graphite carbon sphere is 5 to 20 nm; Preferably, the pore diameter of the graphite carbon sphere is 0.05-1 μm.
3. A method for preparing an electrode slurry as claimed in claim 1 or 2, characterized in that: The preparation method comprises: uniformly mixing the pore additive, active material, conductive additive, binder and solvent to obtain electrode slurry.
4. The method for preparing the electrode slurry according to claim 3, characterized in that: Based on the mass of the non-solvent part in the electrode slurry being 100 wt %, the pore additive accounts for 0.1 to 2 wt % of the non-solvent part in the electrode slurry; Preferably, the preparation method of the graphite carbon sphere comprises: introducing a carbon source into a quartz tube, depositing a graphitized carbon layer on a template by chemical vapor deposition to obtain a template / graphitized carbon layer composite, and then removing the template to obtain the graphite carbon sphere; Preferably, the template comprises any one of silicon dioxide, magnesium oxide, zinc oxide, iron oxide or magnesium carbonate; Preferably, the size of the template is 0.05-1 μm; Preferably, the carbon source comprises a liquid carbon source or a gaseous carbon source; Preferably, the liquid carbon source includes any one of acetonitrile, methanol or ethanol; Preferably, the gaseous carbon source comprises methane or acetylene; Preferably, the heating rate of the chemical vapor deposition is 5 to 20°C / min; Preferably, the temperature of the chemical vapor deposition is ≥700°C; Preferably, the chemical vapor deposition time is 20 to 180 minutes; Preferably, the liquid carbon source is introduced into the quartz tube by an inert gas; Preferably, the flow rate of the inert gas or the gaseous carbon source is 20 to 200 mL / min; Preferably, the inert gas or the gaseous carbon source is introduced before the temperature rise begins, and the ventilation time is 10 to 20 minutes.
5. The method for preparing the electrode slurry according to claim 4, characterized in that: The method for removing the template comprises: etching the template in the template / graphitized carbon layer composite with a solvent to obtain the graphite carbon sphere; Preferably, the solvent comprises sodium hydroxide solution; Preferably, the concentration of the sodium hydroxide solution is 2.5 to 5 mol / L; Preferably, the etching is performed under stirring; Preferably, the etched product is washed with deionized water, filtered and dried.
6. The method for preparing the electrode slurry according to claim 3, characterized in that: The preparation method comprises the following steps: (1) Preparing graphite carbon spheres: placing a template in a quartz tube, introducing a carbon source into the quartz tube at a flow rate of 20 to 200 mL / min for 10 to 20 min, then heating the quartz tube to ≥700°C at a heating rate of 5 to 20°C / min, and depositing a graphitized carbon layer for 20 to 180 min to obtain a template / graphitized carbon layer composite, then preparing a 2.5 to 5 mol / L sodium hydroxide solution, placing the template / graphitized carbon layer composite in the sodium hydroxide solution, etching the template in the template / graphitized carbon layer composite, and then washing the product with deionized water, filtering and drying it in sequence to obtain the graphite carbon spheres; (2) Preparing electrode slurry: The graphite carbon balls, active materials, conductive additives, binders and solvents described in step (1) are mixed evenly to obtain the electrode slurry.
7. A porous electrode, characterized in that: The porous electrode includes a current collector and a porous active material layer located on at least one side of the current collector, and the porous active material layer is obtained by coating the electrode slurry described in claims 1-2 or the electrode slurry prepared by the preparation method described in any one of claims 3-6 onto at least one side of the current collector.
8. The porous electrode according to claim 7, characterized in that The porous electrode includes a porous negative electrode or a porous positive electrode.
9. A method for preparing a porous electrode, characterized in that: The preparation method comprises: applying the electrode slurry as described in claims 1-2 or the electrode slurry prepared by the preparation method as described in any one of claims 3-6 to at least one side surface of the current collector, and obtaining the porous electrode after rolling.
10. Use of the porous electrode according to claim 7 or 8 in a secondary battery.